Caffeine Levels from Various Types of Coffee Drink Packaging Circulated in the Medan City Market Were Examined Using a UV Spectrophotometry Method - Gabena Indrayani Dalimunthe; Adli Nuzula Rahmah; Zulmai Rani; Yayuk Putri Rahayu (Universitas Negeri Medan, 2022)
Coffee drinks are drinks that come from the processing and extraction of coffee beans. One of which is caffeine. Coffee contains approximately 24 of the most important substances. The purpose of this study was to determine the level of caffeine in coffee drinks from various types of packaging. The research stages include sample collection and preparation; identification of caffeine content; and examination of caffeine levels using UV spectrophotometry. The results showed that the three samples of coffee drinks sold at the minimarket in Jermal, Medan contained caffeine, and the levels of caffeine in coffee drinks were 26,352±0,292 mg/100mL (Sample A), 15,179±0,286 mg/100mL (Sample B), and 7,965±0,98 mg/100mL (Sample C). The caffeine content obtained meets the requirements of SNI, where the maximum amount of caffeine that can be consumed by the public in a day based on SNI is 50 mg–150 mg.